How university students in South Africa perceive their fathers’ roles in their educational development - Okeke, C. I. O.; Salami, I. A. (South African Journal of Higher Education, 2021)
The larger study that has influenced this article was designed to explore what influenced rural men’s capabilities to actively participate in children’s early social development and its impact on transition to adulthood among their university-going children. Studies have established an increase in the level at which fathers in South Africa have been found wanting in terms of supporting their children’s development at early stages in their lives. It has been reported that this unacceptable behaviour can be transmitted or carried over from one generation to the next. There is the belief that the majority of the young male children who experienced non-supportive fathers will grow up repeating this behaviour with their children. This calls for a study on the perceptions of young people about what fatherhood is all about, hence this study. This study used a descriptive survey with a sample size of 300 students studying education in one university in the Eastern Cape Province. A 25-item questionnaire titled Perception of Fatherhood by University Students (α = 0.75) was used to collect data that were analysed using descriptive and inferential statistics. The participants perceived that the experience and level of education influence men’s perception of fatherhood positively. Extra‑curricular programmes for proper fatherhood transition of young boys are recommended, commencing from Grade 1 through to Grade 12, to expose them to the kinds of dispositions that will enable them to be responsible fathers. There is also a need for compulsory empowerment programmes such as for designers, artists and sportsmen and other semi-skilled professions for male children who cannot acquire higher education to strengthen them socio-economically to provide education for their children.